The 2D resistivity modelling on north sumatran fault structure by using magnetotelluric data. (November 2019) - Rizal, M; Ismail, N; Yanis, M; Muzakir; Surbakti, M S
Abstract: Aceh is the region that some parts of the Sumatran Fault System ( GSF ) pass through. The existence of faults has implications for earthquake events. To understand the impact of seismic activities that occur along the fault, it is necessary to do fault mapping and geometry modelling. In this study, magnetotelluric geophysical methods were used to describe 2D resistivity structures in the northern Sumatran. A geophysical survey using magnetotelluric method was done to image 2D resistivity model along the northern part of the fault. The measurement was carried out two lines, with a length of the profile is 92 km and 114 km, consisting of 14 measurement points across the fault, with distances between tracks ranging from 10-15 km. 2D resistivity models were generated by using the Reduce Basic Occam (REBOCC) code. From the resulted model, it can be interpreted as indications of the existence of the Aceh Segment and Segment Seulimeum Faults. In-line C, there are two locations indicated by faults, namely Saree area associated with the Seulimeum segment and the Jantho area associated with the Aceh segment and line D in the geographic area is associated with the Aceh segment. From the resulted model, the Sumatran Fault in the northern part of Aceh was divided into two segments as shown in the model.